The Pope and the Pandemic: A Critical Discourse Analysis on America’s COVID-19 Coverage - Novita Dewi; Trly Almendo Pasaribu; Barli Bram (PAROLE: Journal of Linguistics and Education, 2021)
This study explores the ways in which America: The Jesuit Review, one Catholic media in the United Sates represents the COVID-19 pandemic to the believers. Using Critical Discourse Analysis, the analyzed materials include 35 selected articles appeared from March to May 2020 publication. Stylistic devices, discursive practice, and ideological implications are the three main analyzing techniques. The analysis reveals that, first, rhetorical style predominates. Secondly, comforting rather than disabling is the mode used in the reporting. Lastly, Pope Francis as the head of the Catholic Church is the moral reference in his call for faith, hope, and compassion during this pandemic time.